Regularities and models of dynamic thermomechanical behavior of viscoelastic composite materials under complex stress state - Slovikov, S.V.; Yankin, A.S.; Wildemann, V.E.; Babushkin, A.V.; Ilinykh, A.V.; Lobanov, D.S. (Perm Federal Research Centre Journal, 2017)
A series of natural tests of a highly-filled low modulus polymer composite with various kinds of complex mechanical exposure at different temperatures was carried out. New data on the regularities of viscoelastic behavior of composite materials in the form of experimental dependences of viscoelastic parameters were obtained. As a result of investigation of the regularities of thermo- mechanical dynamic behavior of the highly-filled low modulus polymer new data of the effect of loading conditions on viscoelastic parameters were obtained. A phenomenological multi-factor mathematical model to describe viscoelastic behavior of the structural polymeric composite material under complex types of action impact is developed. In the course of scientific research the basis of an experimental and theoretical apparatus of identification of deformative properties of viscoelastic polymers in complex loading conditions was developed, taking into account the features of the latest test systems, measurement tools and application software. A programme of experimental research of dynamic viscoelastic behavior of the material in the conditions close to the operational ones was created. We obtained verified coefficients of the multivariate phenomenological mathematical model to describe viscoelastic behavior of the structural polymer composite.